The heat capacity of nitrogen chain in grooves of single-walled carbon nanotube bundles - Bagatskii, M.I.; Barabashko, M.S.; Sumarokov, V.V. (Физика низких температур, 2013)
The heat capacity of bundles of closed-cap single-walled carbon nanotubes with one-dimensional chains of nitrogen molecules adsorbed in the grooves has been first experimentally studied at temperatures from 2 to 40 K using an adiabatic calorimeter. The contribution of nitrogen CN₂ to the total heat capacity has been separated. In the region 28 K the behavior of the curve CN₂(T) is qualitatively similar to the theoretical prediction of the phonon heat capacity of 1D chains of Kr atoms localized in the grooves of SWNT bundles. Below 3 K the de-pendence CN₂(Т) is linear. Above 8 K the dependence CN₂(Т) becomes steeper in comparison with the case of Kr atoms. This behavior of the heat capacity CN₂(Т) is due to the contribution of the rotational degrees of free-dom of the N₂ molecules.